2016
DOI: 10.1681/asn.2014121226
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Mediated Inhibition of Enzyme Replacement Therapy in Fabry Disease

Abstract: Fabry disease (FD) is a progressive multisystemic disorder, treatable with recombinant enzyme replacement therapy (agalsidase). However, recent studies suggest an endogenous inhibition of agalsidase in patients with FD, as reported for other lysosomal storage diseases. To assess the clinical consequences of serum-mediated agalsidase inhibition in affected patients, we determined the agalsidase inhibition status of 168 patients (68 male) with FD and compared outcomes of inhibition-positive patients with those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 25 publications
7
113
3
Order By: Relevance
“…The number of samples that test positive for neutralizing activity and/or inhibition of uptake is dependent on the sensitivity and specificity of the method (Fabrazyme ® Prescribing information, last updated May 2010). Thus, it is not surprising that neutralizing antibody activity results from this study differ from results reported by other groups (Linthorst et al 2004;Lenders et al 2015). Studies have demonstrated that both agalsidase alfa and agalsidase beta are structurally equivalent and, on a milligram basis, induce similar, fully cross-reactive, antibody responses in vivo (Blom et al 2003;Lee et al 2003;Linthorst et al 2004), refuting the suggestion that variation in glycosylation patterns between agalsidase beta and agalsidase alfa may have implications for the long-term safety of ERT (Barbey et al 2008).…”
Section: Discussioncontrasting
confidence: 42%
“…The number of samples that test positive for neutralizing activity and/or inhibition of uptake is dependent on the sensitivity and specificity of the method (Fabrazyme ® Prescribing information, last updated May 2010). Thus, it is not surprising that neutralizing antibody activity results from this study differ from results reported by other groups (Linthorst et al 2004;Lenders et al 2015). Studies have demonstrated that both agalsidase alfa and agalsidase beta are structurally equivalent and, on a milligram basis, induce similar, fully cross-reactive, antibody responses in vivo (Blom et al 2003;Lee et al 2003;Linthorst et al 2004), refuting the suggestion that variation in glycosylation patterns between agalsidase beta and agalsidase alfa may have implications for the long-term safety of ERT (Barbey et al 2008).…”
Section: Discussioncontrasting
confidence: 42%
“…Some investigators revealed that the elevated plasma lyso-Gb3 level was reduced following ERT and the improvement of some clinical manifestations was associated with it in Fabry patients, suggesting the availability of plasma lyso-Gb3 as an indicator reflecting the efficacy of ERT [3,5,8]. On the other hand, it has been reported that antibodies against recombinant GLAs produced in Fabry patients have a negative impact on the therapeutic effect of the enzymes [9,10]. However, there have been few studies on the relationship between antibodies and plasma lyso-Gb3.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the elevated circulating lysoGb3, considered to be toxic for podocytes and nociceptive neurons, is not completely corrected by present ERT 30,31 . Finally, a complicating factor with present ERT of FD proves to be the antigenicity of recombinant human α-galactosidase A in the majority of male FD patients that lack any endogenous enzyme (25). In these individuals neutralizing antibodies against therapeutic enzyme develop quickly, resulting in a relapse in the reduction of circulating toxic lysoGb3 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most male FD patients lack the α-Gal A protein and consequently develop neutralizing antibodies against the therapeutic recombinant enzymes which might contribute to the noted poor responses to current treatments (24). Indeed, it was recently reported that compared with agalsidase inhibition-negative men, agalsidase inhibition-positive men showed greater left ventricular mass and substantially lower renal function (25). Additionally, these patients presented more often with symptoms such as diarrhea, fatigue, and neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%